Wearable metamaterial dual-polarized high isolation uwb mimo vivaldi antenna for 5g and satellite communications - Alhawari, A.R.H. (MDPI, 2021)
A low-profile Multiple Input Multiple Output (MIMO) antenna showing dual polarization, low mutual coupling, and acceptable diversity gain is presented by this paper. The antenna introduces the requirements of fifth generation (5G) and the satellite communications. A horizontally (4.8â31 GHz) and vertically polarized (7.6â37 GHz) modified antipodal Vivaldi antennas are simulated, fabricated, and integrated, and then their characteristics are examined. An ultra-wideband (UWB) at working bandwidths of 3.7â3.85 GHz and 5â40 GHz are achieved. Low mutual coupling of less than â22 dB is achieved after loading the antenna with cross-curves, staircase meander line, and integration of the metamaterial elements. The antennas are designed on a denim textile substrate with Îµr = 1.4 and h = 0.5 mm. A conductive textile called ShieldIt is utilized as conductor with conductivity of 1.8 Ã 104 . After optimizing the proposed UWB-MIMO antennaâs characteristics, it is increased to four elements positioned at the four corners of a denim textile substrate to be employed as a UWB-MIMO antenna for handset communications, 5G, Ka and Ku band, and satellite communications (X-band). The proposed eight port UWB-MIMO antenna has a maximum gain of 10.7 dBi, 98 radiation efficiency, less than 0.01 ECC, and acceptable diversity gain. Afterwards, the eight-ports antenna performance is examined on a simulated real voxel hand and chest. Then, it is evaluated and compared on physical hand and chest of body. Evidently, the simulated and measured results show good agreement between them. The proposed UWB-MIMO antenna offers a compact and flexible design, which is suitably wearable for 5G and satellite communications applications. Â© 2021 by the authorsLicensee MDPI, Basel, Switzerland.